Rubia cordifolia L. Attenuates Diabetic Neuropathy by Inhibiting Apoptosis and Oxidative Stress in Rats - Sweeti Bana; Nitin Kumar; Ali Sartaj; Abdulsalam Alhalmi; Ashraf Ahmed Qurtam; Fahd A. Nasr; Mohammed Al-Zharani; Neelam Singh; Praveen Gaur; Rosaline Mishra; Snigdha Bhardwaj; Hasan Ali; et al. (MDPI AG, 2023)
Background: Diabetic neuropathy is a debilitating manifestation of long-term diabetes mellitus. The present study explored the effects of the roots of Rubia cordifolia L. (R. cordifolia L.) in the Wistar rat model for diabetic neuropathy and possible neuroprotective, antidiabetic, and analgesic mechanisms underlying this effect. Materials and Methods: Rats were divided into five experimental groups. An amount of 0.25% carboxy methyl cellulose (CMC) in saline and streptozotocin (STZ) (60 mg/kg) was given to group 1 and group 2, respectively. Group 3 was treated with STZ and glibenclamide simultaneously while groups 4 and 5 were simultaneously treated with STZ and hydroalcoholic extract of the root of R. cordifolia, respectively. Hot plate and cold allodynias were used to evaluate the pain threshold. The antioxidant effects of R. cordifolia were assessed by measuring Thiobarbituric acid reactive substances (TBARS), reduced glutathione (GSH), catalase (CAT), and superoxide dismutase (SOD). At the end of the study, sciatic nerve and brain tissues were collected for histopathological study. Bcl-2 proteins, cleaved caspase-3, and Bax were assessed through the Western blot method. Results: R. cordifolia significantly attenuated paw withdrawal and tail flick latency in diabetic neuropathic rats. R. cordifolia significantly (p < 0.01) improved the levels of oxidative stress. It was found to decrease blood glucose levels and to increase animal weight in R. cordifolia-treated groups. Treatment with R. cordifolia suppressed the cleaved caspase-3 and reduced the Bax:Bcl2 ratio in sciatic nerve and brain tissue compared to the diabetic group. Histopathological analysis also revealed a marked improvement in architecture and loss of axons in brain and sciatic nerve tissues at a higher dose of R. cordifolia (400 mg/kg). Conclusion: R. cordifolia attenuated diabetic neuropathy through its antidiabetic and analgesic properties by ameliorating apoptosis and oxidative stress.